Penyuluhan Hukum Adat kepada Masyarakat Desa Tanjung Mudo: Menumbuhkan Kesadaran dan Penguatan Hukum Adat dalam Kehidupan Sosial - Harmaini; Apriadi Bahri, Rizki; Ananda, Tiara (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
Legal counseling on customary law to the community of Tanjung Mudo Village aims to raise awareness about the importance of customary law in their social lives. Customary law, as part of an unwritten legal system, plays a crucial role in regulating social relations and resolving conflicts within indigenous communities. This counseling is carried out using an interactive communication method, involving customary leaders and active participation from local community members. This study demonstrates that the counseling successfully increased the community's understanding of their rights and obligations in the context of customary law, as well as the importance of preserving customary law as part of their cultural identity. Despite challenges in overcoming the differences in understanding between the older and younger generations, the strategies used in the counseling proved effective in fostering a better understanding of customary law and its relevance in everyday life. Therefore, this counseling makes a significant contribution to strengthening customary law as an instrument for resolving social issues and preserving culture in Tanjung Mudo Village.